Distance and Visibility: Two Systems in Hausa Deixis - Abdoulaye, Mahamane L. (Linguistik Online, 2008)
The current standard account of Hausa deixis claims that Hausa has a linear person-based system with the following four locative adverbs and their interpretations: nân ’here’, nan ’there near you’, cân ’there away from you and me’, and can ’over there away from you and me’. This paper shows that in fact one may need two separate deictic systems for Hausa to account for all relevant data. The first system is based on distance with a primary proximal vs. distal contrast. The distance system however also embeds a person subsystem, with one adverb in particular referring to the hearer (second person) position. The second deictic system in Hausa is based on visibility, with a primary contrast between an area comfortably visible and an area visible only with some difficulties. Indeed, in the visibility system, five adverbs range the entire visible area in front of the speaker, from the foreground up to the extreme visible area at the horizon.